Anita Desai critical perspectives - Kohli, Devindra, Ed. (New Delhi Pencraft International, 2008)
Contributed articles on the works of Anita Desai, Indic fiction writer in English.
Includes bibliographical references.
Keywords: Desai, Anita -- Criticism and interpretation